The Harvest of Translations: Errors in Translating Jurisprudential Words by Google Translate - M. Hari Zakiyudin; Muhammad Alfan; Bambang Irawan (Abjadia, 2022)
Everyone agrees that humans and technology are an inseparable part even in the field of education, as well as the use of machine translators to translate one language into another. But unfortunately, it is not comprehensive enough to translate Arabic words because it only looks at the words written above the line. This study aims to detect and describe errors in the translation of Google Translate to words in the science of fiqh so that all the shortcomings and weaknesses appear in front of us so we need to read it a second time. The researcher uses a descriptive approach to obtain good and in-depth research results as he wants to explain. In the end, the results of the study showed errors caused by translating via google which translates jurisprudential words, the error is represented in the translation (1) the word "fashl" in the sense of separation (2) and the word "hajr" which means it is used in everyday life (3) and the word "shodaq" in the translation. the meaning of friendship (4) the word "raj'ah" in the sense of reward (5) the word "al-marrah" in the sense of bitterness (6) the word "ghairu ba'in" with an unclear meaning (7) the word "'iddah" means some. In addition, he cannot distinguish between "ma an-nafiyah" and "ma al-maushuliyyah" which connects until there is confusion about the meaning of obligatory something to be not obligatory